The Influence of Learning Cooperative Models STAD (Student Teams Achievement Division) on Student Cognitive Learning Outcomes - Ikhsan, Muhammad; Esser, Balkis Ratu N L (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to analyze the effect of the cooperative learning model Student Teams Achievement Division (STAD) on students' cognitive learning outcomes in biology subjects. The research employed a quasi-experimental design with a post-test only control group approach. The sample consisted of two classes: an experimental class using the STAD model and a control class using the lecture method. The findings revealed that the average cognitive learning outcomes in the experimental class were higher (63.75) than in the control class (50.52). However, the t-test results showed no statistically significant difference (p > 0.05), indicating that the STAD model did not significantly impact students' cognitive learning outcomes in this context. Factors such as lesson planning, time constraints, and content mastery were the primary challenges in implementing the model. The study recommends improving the application of the STAD model to enhance its effectiveness in future implementations.